Promising Benefits of Ashwamedha Yagya - A Scientific Investigation - Rajani R Joshi (Dr. Chinmay Pandya, 2024)
Scientific aspects and promising applications of yagya are highlighted in this paper in the light of the recent investigations and findings in some modern laboratories. Potential benefits of the Ashwamedha Yagya in Mumbai are discussed with this backdrop. Importance of the unique confluence of the energies generated by yagya and collective rhythmic chanting of the Vedic Mantras is also highlighted with the scope of path-breaking advanced scientific research.